2010
DOI: 10.3109/09638288.2010.481026
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support and depression among Veterans with multiple sclerosis

Abstract: Interventions aimed at increasing positive social interactions, expressed affection and emotional/information support may be particularly helpful for individuals with MS and their caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 45 publications
4
18
0
1
Order By: Relevance
“…A meta-analysis by Schulz and Sherwood (2008) found that family caregivers with limited social support networks de scribed poorer psychological well-being compared to family care givers with more interpersonal resources. Our findings are also consistent with the MS social support literature, which has shown that those who perceived more overall social support also reported fewer depressive symptoms (Bambara, Turner, Williams, & Haselkom, 2011;Dennison, Moss-Morris, & Chalder, 2009). Another finding was that more veteran comorbid health condi tions and greater MS disease severity were associated with more caregiver depressive symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…A meta-analysis by Schulz and Sherwood (2008) found that family caregivers with limited social support networks de scribed poorer psychological well-being compared to family care givers with more interpersonal resources. Our findings are also consistent with the MS social support literature, which has shown that those who perceived more overall social support also reported fewer depressive symptoms (Bambara, Turner, Williams, & Haselkom, 2011;Dennison, Moss-Morris, & Chalder, 2009). Another finding was that more veteran comorbid health condi tions and greater MS disease severity were associated with more caregiver depressive symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…For sociodemographic variables related to depression and perceived social support, we found that younger age reported greater depression. Our findings are parallel with Bambara in which younger individuals with MS are more likely to experience depression compared to their older counterparts. However, our study revealed that even depression is more common in younger age, older MS patients reported that they received higher social support.…”
Section: Discussionsupporting
confidence: 80%
“…The US Armed Forces Veterans who were inflicted with multiple sclerosis were the chosen sample group of Bambara's study . He examined the relationship between the perceived social support and depression of the Veterans.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, of the 25 studies assessing depression , 14 found an inverse association between some element of social support and depression [29, 33, 34, 3739, 42, 5460], six studies reported a trend towards an inverse association [43, 45, 6164], and one observed no association [46]. Two studies tested associations only in bivariable analyses and found no significant correlations [30, 53].…”
Section: Resultsmentioning
confidence: 99%